LIVESTOCK PRODUCTS AND THEIR PROCESSING ISSUES (A CASE STUDY OF THE KASHKADARYA OASIS) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the development of animal husbandry, particularly the Karakul sheep breeding sector, in the Kashkadarya oasis from 1925 to 1991. The study examines the processes of livestock production, processing, and export, as well as the challenges faced and the factors influencing them. Additionally, it explores the increase in the number of Karakul sheep, the growth of Karakul pelt production, breeding activities, and the impact of Soviet policies on these processes.